Challenges in ALK inhibition of ALK-positive non-small-cell lung cancer: from ALK positivity detection to treatment strategies after relapse. (8th August 2018) - Cortinovis, Diego; Canova, Stefania; Abbate, Maria I; Colonese, Francesca; Cogliati, Viola; Bidoli, Paolo
ALK positivity, despite representing only in a small proportion of patients with non-small-cell lung cancer, is worth researching at diagnosis given the possibility to treat these patients with some targeted ALK inhibitors, which are more potent than chemotherapy. Thanks to understanding the resistance mechanisms, newer and more selective inhibitors are now available in clinical practice. Hence, this disease represents, after EGFR inhibition, a largely effective precision medicine approach. However, there are still some clinical situations in which the targeted drug seems to be ineffective. This review discusses some uncertainty about such a 'precision medicine application', focusing on some weaknesses and giving perspectives and suggestions to improve the management of this specific population.